Pelatihan Virtual Menulis Puisi di Masa Pandemi COVID-19 untuk Meningkatkan Budaya Literasi di SMP Negeri 1 Karangampel Kab. Indramayu - Ratna Juwitasari Emha; Varatisha Anjani Abdullah; Tri Pujiati; Yuli Iskandari (Abdi Laksana : Jurnal Pengabdian Kepada Masyarakat, 2020)
Poetry is a reflection of hearts and feelings expressed by humans through literary works. Poetry writing activities can improve students' ability to improve literacy culture. Community Service Activities are carried out as an effort to improve student literacy in SMP Negeri 1 Karangampel, Kab. Indramayu in this technological era so that their work can be read by the general public on social media. This activity is carried out through a virtual method by inviting teachers and students to be actively involved in Community Service activities organized by the academic community of the Indonesian Literature Study Program at Pamulang University. PKM activities carried out on 18-20 June 2020. The results of this PKM activity concluded that basically students in SMP Negeri 1 Karangampel, Kab. Indramayu has a fairly good literacy ability. This is evident from their ability to write and read poetry in public with a bold and the quality of poetry that is made quite good. The expectation of this PKM activity is the quality of writing poetry of students in the school continues to increase and they dare to read poetry and write poetry through social media so that their work can be read by the wider community.Keywords: Poetry, Literacy Culture, Pandemic Era Covid-19